ORBITAL INVOLVEMENT IN SINONASAL DISEASES - Qazi, Zia-us-Salam; Latif, Sarfraz; Awan, Sadia Maqsood (Journal of Ayub Medical College Abbottabad, 2016)
BACKGROUND: The purpose of this study was to: To enlist diagnoses of all the patients with sinonasal disease, in which orbit was also involved unilaterally or bilaterally To analyze the management strategy and final outcome in all the cases MATERIALS & METHODS Hundred consecutive patients having orbital symptoms along with sinonasal complaints that presented in ENT department of Shaikh Zayed federal postgraduate medical institute were included in our prospective study. . CT scan and/or MRI were done in all the cases and ophthalmological consultation was done. Patients having orbital signs and symptoms, which did not show clinical and radiological evidence of sinonasal involvement, were excluded from our study. Final diagnosis was made after histopathological confirmation RESULTS 37% of the patients were diagnosed to be having Allergic fungal rhinosinusitis 16% had mucormycosis, 16% had chronic invasive fungal sinusitis. Other pathologies identified were Nasopharyngeal CA (4%), Squamous cell Ca (4%), cavernous sinus thrombosis (3%), Adenocarcinoma (3%), Angiofibroma (2%) fibrous dysplasia (2%) and Acute complicated Rhinosinusitis (2%) Other rare pathologies that were identified, included lymphoma (1 patient), Osteoma (1 patient), Rhabdomyosarcoma (1 patient), Transitional cell ca arising from inverted papilloma (1 patient), Hemangiopericytoma (1 patient), Spindle cell sarcoma (1 patient), Pituitary adenoma (1 patient), Giant cell sarcoma (1 patient), Malignant undifferentiated tumour, (1 patient), and plexiform neurofibroma (1 patient). One patient was diagnosed to be having sinonasal tuberculosis Most common orbital symptom was proptosis (84%) followed by diplopia (8%), visual loss (4%) and ophthalmoplegia (4%) CONCLUSION Orbital involvement in most of the sinonasal diseases indicate extensive and aggressive nature of the pathology and many of these, even if they are not malignancies are difficult to treat. This is especially true for acute fulminant and chronic invasive fungal rhinosinusitis. Background: Orbital involvement in sinonasal diseases can present as proptosis, ophthalmoplegia or even as blindness due to optic nerve damage. There are a number of sinonasal diseases which can involve eyes. The purpose of this study was to enlist diagnoses of all the patients with sinonasal disease, in which orbit was also involved unilaterally or bilaterally and to analyse the management strategy and final outcome in all the cases. Methods: Hundred consecutive patients having orbital symptoms along with sinonasal complaints that presented in ENT department of Shaikh Zayed federal postgraduate medical institute were included in our prospective study. CT scan and/or MRI were done in all the cases and ophthalmological consultation was done. Patients with sinonasal complaints without clinical involvement of orbit and those with primary orbital pathology were excluded from our study. Final diagnosis was made after histopathological confirmation. Results: A total of 37% of the patients were diagnosed to be having Allergic fungal rhinosinusitis 17% had mucormycosis, 16% had chronic invasive fungal sinusitis. Other pathologies identified were Nasopharyngeal CA (4%), Squamous cell Ca (4%), cavernous sinus thrombosis (3%), Adenocarcinoma (3%), Angiofibroma (2%) fibrous dysplasia (2%) and Acute complicated Rhinosinusitis (2%) Following rare pathologies were identified in only one patient each. These included Lymphoma, Osteoma, Rhabdomyosarcoma, Transitional cell carcinoma arising from inverted papilloma, Hemangiopericytoma, Spindle cell sarcoma, Pituitary adenoma, Giant cell sarcoma, Malignant undifferentiated tumour, Plexiform neurofibroma and sinonasal tuberculosis. Most common orbital symptom was proptosis. Eighty-one patients had proptosis followed by 23 patients with diplopia, 22 patients with ophthalmoplegia, 16 patients with visual loss and 15 patients with ptosis. Conclusion: Orbital involvement in most of the sinonasal diseases indicate extensive and aggressive nature of the pathology and many of these, even if they are not malignancies are difficult to treat. This is especially true for acute fulminant and chronic invasive fungal rhinosinusitis. Keywords: Sinonasal; Orbital; Proptosis; Rhinosinusitis